Paulus retro? - Engberg-Pedersen, Troels (Dansk teologisk tidsskrift, 2012)
Resumé The article discusses claims made in a recent Danish bookentitled Paul Plus – Four Prisms on Paul: Paul Copenhagen: Publications of theFaculty of Theology 30, 2012). Against the contributors, who are basicallypresenting a traditional, Lutheran understanding of Paul in oppositionto the ‘New Perspective on Paul’, it is fi rst argued that not only wasPaul a Jew: he also continued to see himself as a Jew and took the newChrist faith to be an eminently Jewish phenomenon; and secondly thata number of further features of a ‘New Perspective’ on Paul (he speaksethnically about Jews and Gentiles, not about human beings vis-à-visGod; and he envisages an actual fulfi llment of the Mosaic Law amongChrist believers, not a continued state of being simultaneously ‘justifi edand a sinner’) follow directly from the fi rst basic feature.